FROM PRINT TO SCREEN: METHODOLOGY, MEDIA, AND TRANSITION OF QUR’ANIC LEARNING IN INDONESIA - Muhamad Zulfar Rohman (UIN Antasari Banjarmasin, 2019)
This article aims to discuss the shift in the methodology of Qur’anic learning in Indonesia that is influenced by media. There are four cases used to map the contestations in the traditional era: Baghdadi, Qiroati, Iqro ', and Yanbu'a. Those have the same characteristic, namely face-to-face learning which is then challenged by the new media that infiltrate the Islamic world. One of the new media described in this paper is the Qur’anCall that is initiated by the PPPA Daarul Qur’an led by the famous preacher Yusuf Mansur. This is a learning and teaching platform for the Qur'an based on a video call. The character possessed by the Qur’anCall is very different from the traditional methodology. Based on this issue, the author examines the changes in Qur’anic learning in the traditional and modern eras then elaborates the effects that have caused. The finding shows that there are degradations from various performative aspects which are inherent in the traditional methods of Qur’anic learning. Furthermore, the authority of the Qur’anic teacher who was once held by the Qur'anic experts can be in the hands of people with low qualifications.